If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -7 = 9y + -5 Reorder the terms: -7 + 8y = 9y + -5 Reorder the terms: -7 + 8y = -5 + 9y Solving -7 + 8y = -5 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -7 + 8y + -9y = -5 + 9y + -9y Combine like terms: 8y + -9y = -1y -7 + -1y = -5 + 9y + -9y Combine like terms: 9y + -9y = 0 -7 + -1y = -5 + 0 -7 + -1y = -5 Add '7' to each side of the equation. -7 + 7 + -1y = -5 + 7 Combine like terms: -7 + 7 = 0 0 + -1y = -5 + 7 -1y = -5 + 7 Combine like terms: -5 + 7 = 2 -1y = 2 Divide each side by '-1'. y = -2 Simplifying y = -2
| P^2-8p-42=0 | | .9=.4m | | 4(3x-2)+5=45 | | 3(n-8)=2+4n | | 3x^3+6x^2+3x= | | 0=27-3x | | 64=8x | | 34.3=-4.9x^2+39.2x | | 6x-4=34 | | 10x-35=-15 | | 4-8x=-5-5x | | 5y+3=8y-4y | | 2k-5=5k+19 | | 3(4x+8)=96 | | 3y+3y=5y+4 | | 10x-35=15 | | a-36=4a | | 3y^3-18y^2+27y= | | 3y^2-18y^2+27y= | | 2x+9=11+3 | | -x+7-6x+3x=19 | | -5+19=6b-8-5b | | 5a+3=28 | | -5p+8+6p=17 | | -7m+9=-9m-3 | | 25x^2+49y^2= | | 5x-3=2x-27 | | 7y-4=11x-a | | -3(6+6x)=-90 | | 4(v-3)+2=5(v-2)-v | | 7p-6p=-8+11 | | 12x-28=63+7x |